High-throughput drug screening using cell spheroids in superhydrophobic patterned chips - Oliveira, Mariana B. (2012)
High-throughput studies in biotechnology areas such as drug screening and tissue engineering have been carried out mainly in 2D environment. However, the low clinical and biological relevance of 2D models is well known. Both in tissues and tumor masses, cells lie in a 3D configuration organized in the self-secreted microenvironment: the extracellular matrix (ECM). In this milieu, cells interact in a totally natural manner, without the interaction of foreign factors, such as materials. The demand for studies using organotypic models is increasing, in order to improve the relevance of the findings achieved in these areas of study. A solution to create such organotypic models is the in vitro construction of cell spheroids. These are micro-masses of cells formed from a cell suspension, where the attachment of cells to any surface is not promoted. As such, cells tend to attach between themselves and form an organized mass, constituted by cells in combination with ECM. Some types of spheroids are grown in order to mimic tumor models: the living spheroid structure contains a necrotic core, similarly to the native tumors. Cell spheroids are also useful as models for the development of complex microtissues [1], and can also be used as building blocks of larger tissues. Several methods to produce cell spheroids are reported in the literature. The hanging drop method is one of those methods: the cells are pulled to the concave bottom of a hanging droplet by gravity effect, and tend to start the natural organization by cell-cell attachment and production of ECM. We propose the use of superhydrophobic surfaces patterned with wettable regions as platforms for the affordable and scale-up production of cell spheroids by the hanging drop method. Moreover, we used the platform - whose wettable regions are transparent and whose drop has its surface totally exposed to the external media allowing its facilitated manipulation – as high-throughput screening platform for drug testing and on-chip cell response analysis by microscopy. For the proof-of-concept we dispensed cell suspensions of distinct cell types (L929 and SaOs-2) with different cell concentrations in the array of wettable regions of the chips. We tested the effect of a cytostatic drug used in clinical practice (doxorubicin), also dispensed in a combinatorial logic in each spot of the chip. By on-chip microscopy analysis we proved the suitability of such platforms for drug screening using tumor-like models.